(untitled) (Herald of the National Children’s Medical Center, 2022)
Enuresis is a very common problem in children, accompanied by impaired social adaptation, thereby reducing the quality of life and self-con=dence of children with this pathology. Treatment of bedwetting is a rather complicated problem that requires correct diagnosis. This article studied the causes of enuresis and the use of a complex of drug and non-drug treatment with elements of acupuncture, herbal medicine and their results.